Wakefield spectra in the plasma-dielectric accelerator when changing the plasma density - Kniaziev, R.R.; Markov, P.I.; Onishchenko, I.N.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2015)
The analysis of the changes in the spectra of a wake field excited in a cylindrical plasma-dielectric waveguide by relativistic electron bunch is carried out. Three variants of structures are considered: the parameters of the dielectric structure and bunches are fixed; inner or outer radius of the dielectric tube is changed, so that the frequency of the first radial mode coincides with the frequency of the plasma wave. The latter two options are necessary in the case of a regular sequence of bunches to increase the amplitude of the wakefield. It is shown that in case of changes in the outer radius an increase in amplitude of the dielectric wave is due to the transformation of the multimode dielectric wave in a monochromatic wave, with the first harmonic, synchronous with the sequence of bunches. Проведений аналіз зміни спектрів кільватерного поля, збуджуваного в циліндричному плазмово-діелектричному хвилеводі релятивістськими електронними згустками. Розглянуто три варіанти структур: параметри діелектричної структури й згустків фіксовані; внутрішній або зовнішній радіуси діелектричної трубки змінюються так, що частота першої радіальної моди збігається із частотою плазмової хвилі. Останні два варіанти необхідні у випадку використання регулярної послідовності згустків для збільшення амплітуди кільватерного поля. Показано, що у випадку зміни зовнішнього радіуса ріст амплітуди діелектричної хвилі пов'язаний із трансформацією багатомодового спектра діелектричної хвилі в одномодовий з першою гармонікою, яка синхронна з послідовністю згустків. Проведен анализ изменения спектров кильватерного поля, возбуждаемого в цилиндрическом плазменно-диэлектрическом волноводе релятивистскими электронными сгустками. Рассмотрены три варианта структур: параметры диэлектрической структуры и сгустков фиксированы; внутренний или внешний радиусы диэлектрической трубки изменяются так, что частота первой радиальной моды совпадает с частотой плазменной волны. Последние два варианта необходимы в случае использования регулярной последовательности сгустков для увеличения амплитуды кильватерного поля. Показано, что в случае изменения внешнего радиуса рост амплитуды диэлектрической волны связан с трансформацией многомодового спектра диэлектрической волны в одномодовый с первой гармоникой, синхронной с последовательностью сгустков.